PERTANGGUNG JAWABAN KORPORASI TERHADAP KEBAKARAN HUTAN DALAM KAITANNYA DENGAN PENERAPAN HUKUM LINGKUNGAN (STUDI KASUS PUTUSAN PENGADILAN NEGERI PELALAWAN NO. 228/PID.SUS/2013/PN.PLW) - Surya Sofyan Hadi; Suhaidi Suhaidi; Syamsul Arifin; Mahmud Mulyadi (USU LAW JOURNAL, 2016)
ABSTRACT Due to the actors who burn the forest to open land oil palm plantation company allegedly is a corporation, the corporation issues related to speak also to the issue of accountability. In terms of corporate accountability is possible through the doctrine of strict liability which, in this teaching criminal liability can be imposed on perpetrators of criminal acts in question with no need to prove the existence of fault (intent or negligence) actors. But the emphasis placed on it, as a result of his actions have caused loss to the community. Suffice if proven that the offender has committed an unlawful act, or not doing that is required by the criminal provisions (offenses of strict liability). Keywords    :  Corporate Liability; Forest fires; and Application of Environmental Law